1993
DOI: 10.1111/j.1438-8677.1993.tb00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Localization and Spectral Characteristics of the Fluorescence Emission of Differently Pigmented Wheat Leaves

Abstract: Intensity, spectral characteristics and localization of the UV‐laser (337 nm) induced blue‐green and red fluorescence emission of green, etiolated and white primary leaves of wheat seedlings were studied in a combined fluorospectral and fluoromicroscopic investigation. The blue‐green fluorescence of the green leaf was characterized by a maximum near 450 nm (blue region) and a shoulder near 530 nm (green region), whereas the red chlorophyll fluorescence exhibited maxima in the near‐red (F690) and far‐red (F735)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…3). Its blue fluorescent spectrum (maximum emission at 475–480 nm) was consistent with the fluorescence properties (36,54,55) of wall‐bound p ‐coumaric, ferulic and caffeic acids (Table 2). Interestingly, sun and shade leaves did not show substantial variations in the concentration of wall‐bound phenylpropanoids, which included flavonoids in addition to hydroxycinnamic acids (Table 2).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…3). Its blue fluorescent spectrum (maximum emission at 475–480 nm) was consistent with the fluorescence properties (36,54,55) of wall‐bound p ‐coumaric, ferulic and caffeic acids (Table 2). Interestingly, sun and shade leaves did not show substantial variations in the concentration of wall‐bound phenylpropanoids, which included flavonoids in addition to hydroxycinnamic acids (Table 2).…”
Section: Resultssupporting
confidence: 75%
“…3). For example, the blue fluorescence of wall‐bound p ‐coumaric, ferulic and caffeic acids (54,59,63), which almost exclusively contributed to the fluorescence spectrum of full‐shade leaves (Tables 1 and 2), partly overlapped with the red‐fluorescing glycosides of quercetin and luteolin (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…These differences were quantified by forming the fluorescence ratios blue/red, blue/far-red, red/far-red and blue/green. By measuring the fluorescence emission spectra of various leaf parts with and without leaf veins in a conventional fluorometer it was demonstrated that the blue-green fluorescence emission, which is thought to emanate exclusively from the cell walls (Stober and Lichtenthaler, 1993a), is primarily emitted from the main leaf vein and to a lower degree also from the lateral leaf veins. In contrast, the contribution of the intercostal fields to the blue-green fluorescence emission of the leaf was low and seems to primarily derive from the leaf epidermis (confer Stober and Lichtenthaler, 1993a).…”
Section: Discussionmentioning
confidence: 99%
“…Upon UV excitation, both young and matured leaves emit red (R), green (G), and blue (B) fluorescence. These fluorescence characteristics have been normally observed for plant leaves, where the B and G fluorescence with the peak of 450-520 nm might be assigned to ferulic and hydroxycinnamic derivatives bound to the cell wall or mesophyll, and R fluorescence is originated from chlorophylls inside the chloroplast [26][27][28]. Interestingly, as shown in Figs.…”
Section: Total Antioxidant Capacitymentioning
confidence: 84%